Just meme it an exploration of the influential power of satirical Facebook memes on the perceptions and attitudes of BBM voters - Chavez, Raphael C.; Tadlip, Prian T.; Carreon, Shane L. (Cebu City College of Communication, Art, and Design , University of the Philippines Cebu, 2024)
In the 2022 Philippine elections, political humor through Memes was used as both a propaganda tool and publicity stunt to elicit reactions and enable people to participate in political discourse while minimizing the direct expression of views and opinions. Political memes, characterized by their aggressiveness in ridiculing and satirizing figures of power and other members of the political elite, for their undesirable qualities and practices (Calimbo, 2015), are the focus of this study. This study investigates the influence of Political satire Memes on the perceptions and attitudes of Bongbong Marcos (BBM) Voters. Utilizing an in-depth semi-structured interview approach, the study aims to engage with 22 BBM Voters residing in Cebu City and Butuan City. This study draws upon Agenda-setting theory, Elaboration Likelihood Model (ELM), and Cognitive Dissonance theory to provide a theoretical framework for analysis.
Thesis (Bachelor of Arts in Communication)--UP Cebu, May 2024.
Includes bibliographical references and appendices.